KEY ASPECTS OF DEVELOPING THE PROFESSIONAL READINESS OF STUDENTS, AS FUTURE TEACHING PROFESSIONALS, TO WORK WITH GIFTED CHILDREN AND YOUNG PEOPLE - Yakovyshyn, Ruslan; Lakhtionova, Liudmyla (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article presents an analysis of the main approaches to the problem of training future teachers to work with gifted children and young people; it reveals the characteristics of the system-forming factors in the construction of a system for training teaching staff to teach and educate gifted children; it defines the basic components of their psychological and pedagogical readiness to develop giftedness.